The X-SHOOTER Lyman α survey at z = 2 (XLS-z2) I: what makes a galaxy a Lyman α emitter?. Issue 1 (10th May 2021) - Matthee, Jorryt; Sobral, David; Hayes, Matthew; Pezzulli, Gabriele; Gronke, Max; Schaerer, Daniel; Naidu, Rohan P; Röttgering, Huub; Calhau, João; Paulino-Afonso, Ana; Santos, Sérgio; Amorín, Ricardo
ABSTRACT: We present the first results from the X-SHOOTER Lyman α survey at z = 2 (XLS- z 2). XLS- z 2 is a deep spectroscopic survey of 35 Lyman α emitters (LAEs) utilizing ≈90 h of exposure time with Very Large Telescope/X-SHOOTER and covers rest-frame Ly α to H α emission with R  ≈ 4000. We present the sample selection, the observations, and the data reduction. Systemic redshifts are measured from rest-frame optical lines for 33/35 sources. In the stacked spectrum, our LAEs are characterized by an interstellar medium with little dust, a low metallicity, and a high ionization state. The ionizing sources are young hot stars that power strong emission lines in the optical and high-ionization lines in the ultraviolet (UV). The LAEs exhibit clumpy UV morphologies and have outflowing kinematics with blueshifted Si ii absorption, a broad [O iii ] component, and a red-skewed Ly α line. Typically, 30 per cent of the Ly α photons escape, of which one quarter on the blue side of the systemic velocity. A fraction of Ly α photons escape directly at the systemic suggesting clear channels enabling an ≈10 per cent escape of ionizing photons, consistent with an inference based on Mg ii . A combination of a low effective H i column density, a low dust content, and young starburst determines whether a star-forming galaxy is observed as an LAE. The first is possibly related to outflows and/or a fortunate viewing angle, while we find that the latter two in LAEs are typical for their stellar mass of 10 9 M⊙ .